The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1139/o92-011
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid uptake in Candida tropicalis: induction of a saturable process

Abstract: The rates of oleate uptake by Candida tropicalis cells grown on a high oleate concentration (3.5 mM oleate in the presence of 0.50% Brij 58) were higher than those observed in cells grown on glucose; however, oleate uptake was not saturable with substrate concentration. Cells grown at a low oleate concentration (1.0 mM oleate and 2.5% Brij 58) grew to a lower density and at a slightly slower rate; these cells were found to take up oleate at a rate 43-fold higher than cells grown on high oleate concentration. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
5
8
0
Order By: Relevance
“…Likewise at 30°C, both strains had comparable apparent K t values (63.5 M for fat1⌬ and 61.5 M for FAT1). These calculated K t values at 30°C are similar to those previously defined in S. cerevisiae and C. tropicalis (17,19). These data are consistent with the notion that Fat1p functions to maximize oleate uptake.…”
Section: Incorporation Of Exogenous Fatty Acids Into Phospholipids Insupporting
confidence: 90%
See 1 more Smart Citation
“…Likewise at 30°C, both strains had comparable apparent K t values (63.5 M for fat1⌬ and 61.5 M for FAT1). These calculated K t values at 30°C are similar to those previously defined in S. cerevisiae and C. tropicalis (17,19). These data are consistent with the notion that Fat1p functions to maximize oleate uptake.…”
Section: Incorporation Of Exogenous Fatty Acids Into Phospholipids Insupporting
confidence: 90%
“…Kohlwein and Paltauf (16) demonstrated that fatty acid uptake in Saccharomyces uvarum and Saccharomycopsis lipolytica occurs via a saturable process. The same observations were made in Candida tropicalis supporting the hypothesis that fatty acid transport is a facilitated process (17). Knoll et al (19) have shown the uptake of exogenous long-chain fatty acids in S. cerevisiae is saturable and that uptake and activation to CoA thioesters are separable.…”
supporting
confidence: 65%
“…In view of the different growth conditions employed, these kinetic values for wild-type cells are comparable to those previously reported for S. cerevisiae wild-type cells, i.e. 6.54 nmol/minute/10 8 cells (Faergeman et al, 1997;Knoll et al, 1995;Trigatti et al, 1992).…”
Section: Fatty-acid Uptake Is Temperature Dependentsupporting
confidence: 87%
“…This assay thus recapitulates key properties of fatty-acid uptake by fungal cells, which have been reported before (Faergeman et al, 1997;Knoll et al, 1995;Kohlwein and Paltauf, 1984;Trigatti et al, 1992).…”
Section: Fatty-acid Uptake Is Temperature Dependentsupporting
confidence: 65%
“…These results in combination with our results could explain, in part, the small linoleic acid transfer found in basal plasma membrane, in vitro. In other tissues and whole cells, a saturable transport system recognizes fatty acids with high affinity, and with a K , value in the range 4.5 -16 pM in cultured cardiac cells [27], K, values ranging from 0.3-0.5 pM in adipocytes [37, 381 and a K, value of 56 pM in Candida tropicalis [34]. In these systems, the V, , , values varied from 2.4 pmol .…”
Section: Membrane Markersmentioning
confidence: 99%